Fuel-saving plate-electrode base device on gasoline fuel engine - Mohamad Sazman, Sazali (2010)
This report shows the design and fabrication of the fuel-saving plate-electrode device on gasoline fuel engine. The objective of the report is to develop the procedures to design and fabricate the fuel-saving plate-electrode base device on gasoline fuel engine. Design generation is showed and solid three dimensional structures modelling of the test rig was developed with the solid work software. Material selection and the reason behind the selection are shown based on criteria predetermined. Based on the selection, plastic and steel are selected. This project is difficult to make because it is hard to find the references and information of similar project. As the conclusion, this project has achieved its goal through the successful of the product making.